Legal Policy of Independent Learning Independent Campus (MBKM) Program in Indonesia: Tracing the Literature - M Afif Hasbullah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The notion of MBKM allows students to choose their learning activities. It takes the willingness of lecturers to respond to this policy to succeed. In the development of the MBKM, there are pros and cons and cons in the community, so a clear legal umbrella is needed to accommodate the policy. This study uses an approach with data collection through library searches sourced from electronic journal articles. After getting a number of articles, the articles that meet the requirements with a data inclusion strategy are selected and then analyzed descriptively. From the selection process, 10 articles were taken as the data and analyzed using content analysis. The results of the study show that the independent campus policy is a government breakthrough in providing autonomy and independence to each university from complicated employees and also giving students the freedom to choose their own study program. In its development, this policy took the form of reaping the pros and cons in the community so that several legal umbrellas were made that could accommodate them, but in the author's view the legal umbrella is still very important because only ministerial regulations need to be made such as laws or higher regulations of government.